Gender-specific associations between tobacco use and body mass index among school-going adolescents in Malaysia: results from the National Health Morbidity Survey 2017 - Zamtira Seman; Jayvikramjit Singh M.S.; Ridwan Sanaudi; Nor Hazimah Yeop Abd Rashid; Mohd Azahadi Omar (Universiti Kebangsaan Malaysia, 2025)
Tobacco uses and obesity are major global public health concerns, with adolescence being a critical period for the onset of these risk factors. In Malaysia, rising trends in adolescent smoking and obesity necessitate further investigation. This study examined gender-specific associations between different types of tobacco use and body mass index (BMI) among school-going adolescents. Data were derived from the NHMS 2017, a nationwide cross-sectional survey using a two-stage stratified random sampling design (N=27,497). Complex sample logistic regression was employed to assess the odds of past 30-day tobacco use by BMI category (underweight/normal weight, overweight, obese) stratified by gender. Confounders, including age, ethnicity, physical activity, fast food consumption, and mental health, were controlled for in the analysis. Adolescents classified as obese had a significant association with tobacco use, but this was not observed in overweight individuals. Male smokers were significantly less likely to be obese, whereas female smokers had a higher likelihood of obesity (AOR = 1.59, 95% CI: 1.25–2.02). Specifically, female users of e-cigarettes (AOR = 1.86, 95% CI: 1.36–2.56), smokeless tobacco (AOR = 1.66, 95% CI: 1.14–2.43), and other tobacco products (AOR = 1.62, 95% CI: 1.05–2.52) exhibited a higher risk of obesity. No significant association was found among male smokers. Female adolescent smokers showed a greater likelihood of obesity, emphasizing the need for gender-specific interventions. To mitigate these risks, public health efforts should incorporate education, policy measures, and lifestyle promotion. Further research is warranted to explore underlying biological mechanisms.